Altered brain function directly related to structural abnormalities in people at ultra high risk of psychosis: longitudinal VBM-fMRI study. - Fusar-Poli, P; Broome, MR; Woolley, J; Johns, L; Tabraham, P; Bramon, E; Valmaggia, L; Williams, S; McGuire, P (2011)
BACKGROUND: Several studies have indicated that people with prodromal signs of psychosis show alterations in the structure and function of the brain when they first present to clinical services. However, the longitudinal course of these abnormalities, and how they relate to subsequent clinical and functional outcome is relatively unclear. METHODS: A cohort of subjects at ultra high risk of psychosis were studied using functional magnetic resonance imaging (fMRI) in conjunction with the N-Back task, and volumetric MRI at first clinical presentation and again after one year. Levels of psychopathology and global functioning were assessed at the same time points using the CAARMS, PANSS, and the GAF scale. RESULTS: At baseline, the high risk group showed reduced activation during the task in the left middle frontal gyrus, supramarginal gyrus and inferior parietal lobule, and reduced gray matter volume in the left middle and medial frontal gyri, left insula and the right anterior cingulate gyrus. Within the high-risk group, there was a positive correlation between the magnitude of the functional and structural alterations in the left middle frontal gyrus. Between presentation and follow up, the severity of perceptual disorder and thought disorder (rated by the CAARMS), and of general psychopathology (rated by the PANSS general score) decreased, and the level of global functioning improved. This clinical and functional improvement was associated with a longitudinal increase in activation in the anterior cingulate and right parahippocampal gyrus. The change in anterior cingulate response was directly correlated with the improvement in the GAF score. CONCLUSIONS: In subjects presenting with prodromal signs of psychosis, reduced prefrontal activation during a working memory task is associated with a reduction in gray matter volume in the same area. Changes in anterior cingulate activation were correlated with functional improvement in this group, consistent with the role of this region in multiple cognitive and social processes.